Applicability of Transcutaneous Oxygen Tension Measurement in the Assessment of Chronic Limb-Threatening Ischemia. (March 2020) - Leenstra, Bernard; Wijnand, Joep; Verhoeven, Bart; Koning, Olivier; Teraa, Martin; Verhaar, Marianne C.; de Borst, Gert J.
Transcutaneous oxygen tension measurement (TcPO2 ) is widely applied for the evaluation of chronic limb-threatening ischemia (CLTI). Nevertheless, studies that focused on the clinical value of TcPO2 have shown varying results. We identified factors that potentially play a role in TcPO2 measurement variation such as probe placement, probe temperature, and the use of a reference probe. In this review of the current literature, we assessed the application of these factors. A systematic search was conducted. Parameters that were assessed were probe placement, probe temperature, and mentioning and/or use of a reference probe. In total, 36 articles were eligible for analysis. In 24 (67%) studies, probes were placed on specific anatomical locations. Seven (19%) studies placed probes, regardless of the location of the ulcer, adjacent to an ischemic lesion or ulcer (perilesion). Selected temperature setting of the probe differed; in 18 (50%), a default probe temperature of 44°C was selected, and in 13 (36%), a different temperature was selected. In 31 (84%) studies, the use of a reference probe was not reported. Transcutaneous oxygen tension measurement is applied diversely in patients with CLTI. Homogeneity in TcPO2 protocols is warranted for reliable clinical application and to compare future TcPO2 research.